SISTEM PENGENDALIAN INTERN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN ASET DAERAH KABUPATEN KUBU RAYA - B51112151, Muhammad Riyansyah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This undergraduate thesis entitled "Internal Control Systems Land and Building Tax Collection in the Revenue Department of the Regional Asset Finance (DPPKAD) Kubu Raya Kubu Raya" which aims to determine the internal control system of collection system property tax (PBB) in the Revenue Department of the Regional Asset Finance (DPPKAD) and to investigate what factors system that affects land and building tax (PBB) in the Revenue Department of the Regional Asset Finance (DPPKAD) Kubu Raya. Research methods used in this study is a case study with data collection techniques among others, by observation, literature study, study documentation and interviews. The analytical tool used in this research is the analysis of the organizational structure, flowcharts, internal control questionnaire (ICQ), and the compliance test. Based on the analysis of organizational structure, flowcharts, internal control questionnaire (ICQ) and compliance test is known that the internal control system of the UN tax on DPPKAD Kubu Raya has generally been quite effective. It is also unknown factors that influence UN voting system in Kubu Raya DPPKAD outline is a clear lack of socialization of local governments, especially in Kubu Raya to the public or the taxpayer, the lack of establishment of the places shown to make payments, and in collecting only expect the realization by the taxpayer to make payment of the United Nations. Keywords: Internal Control Systems Land and Tax Collection Building